A modified algorithm for the homotopy perturbation method with applications to Lotka-Volterra systems - Chowdhury, Md. Sazzad Hossien; Hassan, Talib Hashim; Ismail, Ahmad Faris (2010)
In this paper, the homotopy-perturbation method (HPM) is modified in order to obtain the approximate solutions of the nonlinear differential equation response in a sequence of time intervals. The modified method provides a solution close to the exact one within a certain error. The accuracy of this method is examined by comparison with the Adomian decomposition method (ADM). The results prove that the modified HPM is a powerful tool for the solution of nonlinear equations.